Dexamethasone can attenuate the pulmonary inflammatory response via regulation of the lncH19/miR-324-3p cascade - Ye Chen; Chao Zhang; Chang-xue Xiao; Xiao-dong Li; Zhi-li Hu; Shou-di He; Xiao-jun Xiao; Feng Xu (BMC, 2021)
Abstract Objective To investigate lncRNAs and their roles in regulating the pulmonary inflammatory response under dexamethasone (Dex) treatment. Methods IL-1β (10 ng/mL) and LPS (1 μg/mL) was used to construct inflammatory cell models with A549 cells; IL-1β performed better against LPS. Different concentrations of Dex were used to attenuate the inflammation induced by IL-1β, and its effect was assessed via RT-PCR to detect inflammatory cytokine-related mRNA levels, including those of IKβ-α, IKKβ, IL-6, IL-8, and TNF-α. Furthermore, ELISA was used to detect the levels of the inflammatory cytokines TNF-α, IL-6, and IL-8. RT-PCR was used to quantify the levels of lncRNAs, including lncMALAT1, lncHotair, lncH19, and lncNeat1. LncH19 was most closely associated with the inflammatory response, which was induced by IL-1β and attenuated by Dex. Among the lncRNAs, the level of lncH19 showed the highest increase following treatment with 1 and 10 μM Dex. Therefore, lncH19 was selected for further functional studies. LncH19 expression was inhibited by shRNA transduced with lentivirus. Cell assays for cell proliferation and apoptosis as well as RT-PCR, western blot, and ELISA for inflammatory genes were conducted to confirm the functions of lncH19. The predicted target miRNAs of lncH19 were hsa-miR-346, hsa-miR-324-3p, hsa-miR-18a-3p, hsa-miR-18b-5p, hsa-miR-146b-3p, hsa-miR-19b-3p, and hsa-miR-19a-3p. Following estimation via RT-PCR, hsa-miR-346, hsa-miR-18a-3p, and hsa-miR-324-3p showed consistent patterns in A549 NC and A549 shlncH19. An miRNA inhibitor was transfected into A549 NC and A549 shlncH19 cells, and the expression levels were determined via RT-PCR. hsa-miR-324-3p was inhibited the most compared with hsa-miR-346 and hsa-miR-18a-3p and was subjected to further functional studies. RT-PCR, ELISA, and western blotting for inflammatory gene detection were conducted to validate the functions of the target hsa-miR-324-3p. Results Treatment with 1 and 10 μM Dex could effectively attenuate the inflammatory response. During this process, lncH19 expression significantly increased (P < 0.05). Therefore, treatment with 1 μM Dex was used for further study. Under IL-1β treatment with or without Dex, lncH19 inhibition led to an increase in cell proliferation; a decrease in cell apoptosis; an increase in the protein levels of inflammatory genes; phosphorylation of P65, ICAM-1, and VCAM-1; and increase inflammatory cytokines. Prediction of the targets of lncH19 and validation via RT-PCR revealed that miR-346, miR-18a-3p, and miR-324-3p negatively correlate with lncH19. Additionally, Dex increased the lncH19 expression but reduced that of the miRNAs. Among the miRNAs, miR-324-3p was the most markedly downregulated miRNA following treatment of miRNA inhibitors. The MTS assay and cell apoptosis assay showed that the miR-324-3p inhibitor inhibited cell proliferation and induced cell apoptosis, thereby significantly attenuating the inflammatory response, which reversed the effect of lncH19 in regulating cell proliferation and the secretion of inflammatory cytokines (P < 0.05). Therefore, lncH19 might regulate miR-324-3p in pulmonary inflammatory response under Dex treatment. Conclusion Dex can attenuate the pulmonary inflammatory response by regulating the lncH19/miR-324-3p cascade.